Kebijakan Pemerintah Dalam Penanggulangan Dampak Covid-19 di Suralaga, Lombok Timur (Studi Pada Pemulihan Ekonomi Pekerja Migran) - Saipul Hamdi; Oryza Pneumatica Indrasari; Syarifuddin; Moh Adiyat Hidayatullah (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2022)
This article aims to understand government policies in tackling the impact of the Covid-19 Pandemic on the economy of migrant workers and their recovery efforts. To overcome the impact of the Covid-19 pandemic so as not to cause a prolonged crisis and minimize the impacts in other sectors, the government needs a social security policy for the economic stability of the community, especially for migrant workers. To understand in more detail about government policies and their implementation, this study aims to explore the implementation model in the economic recovery of the community, especially the Indonesian Migrant Workers (PMI) group. This research was conducted for 6 months (October-March 2022) using qualitative methods. Data was collected using participant observation techniques, in-depth interviews, FGDs, and documentation. There were 30 informants in the study (15 men and 15 women) consisting of migrant workers, village governments, local governments, NGOs, and migrant workers distributors. The results of this study indicate that Covid-19 has had a major impact on the weakening of the community’s economy, including groups of migrant workers. In addition, the village governments in the Suralaga sub-district, namely the villages of Suralaga, Paok Lombok and Dasan Borok, have successfully implemented policies from the central government in order to mitigate the economic impact of Covid-19, especially for groups of Indonesian migrant workers. In addition to continuing central programs such as providing BLT (Direct Cash Assistance) and basic necessities, the village governments in theose three villages made special policies as a solution to the economic problems that occurred to groups of Indonesian migrant workers, namely providing assistance to PMIs who were affected by disasters in their countries of work, providing illegal access to PMI during Covid-19, Micro, Small and Medium Enterprises (MSME) development, agricultural assistance, and livestock. Abstrak Artikel ini bertujuan untuk memahami kebijakan pemerintah dalam menanggulangi dampak pandemi Covid-19 terhadap ekonomi pekerja migran dan upaya pemulihannya. Untuk menanggulangi dampak pandemi Covid-19 ini agar tidak menimbulkan krisis yang berkepanjangan dan meminimalisir dampak-dampak di sektor lainnya, maka pemerintah membutuhkan suatu kebijakan pengamanan sosial untuk kestabilan ekonomi masyarakat, terutama bagi buruh migran. Untuk memahami lebih detail tentang kebijakan pemerintah dan implementasinya, maka penelitian ini bertujuan untuk mengeksplorasi model implementasinya dalam pemulihan ekonomi masyarakat khusunya kelompok pekerja migran Indonesia (PMI). Penelitian ini dilakukan selama 6 bulan (Oktober-Maret 2022) dengan menggunakan metode kualitatif. Pengumpulan data dilakukan dengan teknik observasi partisipan, wawancara mendalam, FGD, dan dokumentasi. Informan dalam penelitian sebanyak 30 orang (15 laki-laki dan 15 perempuan) terdiri dari pekerja migran, pemerintah desa, pemerintah daerah, LSM, dan penyalur TKI. Hasil penelitian ini menunjukan bahwa Covid-19 berdampak besar pada melemahnya ekonomi masyarakat termasuk kelompok pekerja migran. Selain itu, pemerintah desa di Kecamatan Suralaga yakni Desa Surala, Paok Lombok dan Dasan Borok berhasil mengimplementasikan kebijakan-kebijakan dari pemerintah pusat dalam rangka penanggulangan dampak ekonomi akibat Covid-19 khususnya bagi kelompok pekerja migran Indonesia. Selain melanjutkan program pusat seperti pemberian BLT (Bantuan Langsung Tunai) dan sembako, pemerintah desa di tiga desa tersebut membuat kebijakan khusus sebagai solusi atas persoalan ekonomi yang terjadi pada kelompok pekerja migran Indonesia yaitu memberi bantuan kepada PMI yang terkena musibah di negara tempat bekerja, memberikan akses ilegal kepada PMI selama Covid-19, pengembangan UMKM, bantuan pertanian, peternakan.